The Encounter of Chinese and Western Philosophies A Critique - Vermander, Benoît (De Gruyter, 2023)
This book revisits the encounter between Chinese and Western philosophy while unfolding questions about the way "comparative philosophy" is conducted today. The currently dominant exegesis organizes philosophical landmarks in pairs of opposites between the Western and Chinese traditions. This book sketches a way of engaging philosophical resources coming from different terroirs to contribute in the shaping of a networked global wisdom.